Oxidation of 5-hydroxytryptamine and related compounds by mytilus gill plates - Blaschko, H. (1960)
Homogenates of gill plates of Mytilus edulis L. used oxygen when 5-hydroxytryptamine was added. The oxidation of 5-hydroxytryptamine was not due to the presence of an amine oxidase, but to that of an enzyme that catalysed the oxidation of other 5-hydroxyindoles (5-hydroxytryptophan, bufotenine). The oxidation was cyanide-sensitive, but was not inhibited by iproniazid. In the reaction a yellowish-brown substance was formed. The occurrence of an amine oxidase in the anterior retractor muscle of the byssus and in the digestive gland was confirmed.